THE ROLE OF CALIPH AL-HAKAM AL-MUSTANṢIR IN ISLAMIC EDUCATION IN CORDOVA, ANDALUSIA - Pramadi Pramadi; Muhammad Tomi; Ellya Roza (International Journal of Teaching and Learning, 2025)
This study examines the role of Caliph Al-Hakam II in advancing Islamic education in Cordova, Andalusia, during the golden age of Islamic civilization. Using a library research method and a qualitative approach, the findings indicate that Al-Hakam II made a substantial contribution to the development of knowledge through the establishment of the University of Cordova as a global intellectual center, the construction of a major library containing approximately 400,000 books, and the encouragement of translations of Greek and Latin works into Arabic. He also invited scholars from various regions to teach and engage in scholarly discussions, as well as provided free education for the community. His visionary policies transformed Cordova into the largest center of knowledge and culture in Europe in the tenth century CE, while simultaneously exerting a major effect on the rise of Western civilization. The leadership of Al-Hakam II demonstrates that education is the primary foundation for building an advanced Islamic civilization.